Cognitive impairment in post-acute sequelae of COVID-19 and short duration myalgic encephalomyelitis patients is mediated by orthostatic hemodynamic changes - Day, Heather; Yellman, Brayden; Hammer, Sarah; Rond, Candace; Bell, Jennifer; Abbaszadeh, Saeed; Stoddard, Greg; Unutmaz, Derya; Bateman, Lucinda; Vernon, Suzanne D. (Frontiers in Neuroscience, 2023)
Introduction Cognitive impairment is experienced by people with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and post-acute sequelae of COVID-19 (PASC). Patients report difficulty remembering, concentrating, and making decisions. Our objective was to determine whether orthostatic hemodynamic changes were causally linked to cognitive impairment in these diseases. Methods This prospective, observational cohort study enrolled PASC, ME/CFS, and healthy controls. All participants underwent clinical evaluation and assessment that included brief cognitive testing before and after an orthostatic challenge. Cognitive testing measured cognitive efficiency which is defined as the speed and accuracy of subject’s total correct responses per minute. General linear mixed models were used to analyze hemodynamics and cognitive efficiency during the orthostatic challenge. Additionally, mediation analysis was used to determine if hemodynamic instability induced during the orthostatic challenge mediated the relationship between disease status and cognitive impairment. Results Of the 276 participants enrolled, 256 were included in this study (34 PASC, 71 < 4 year duration ME/CFS, 69 > 10 year ME/CFS duration, and 82 healthy controls). Compared to healthy controls, the disease cohorts had significantly lower cognitive efficiency scores immediately following the orthostatic challenge. Cognitive efficiency remained low for the >10 year ME/CFS 2 and 7 days after orthostatic challenge. Narrow pulse pressure less than 25% of systolic pressure occurred at 4 and 5 min into the orthostatic challenge for the PASC and ME/CFS cohorts, respectively. Abnormally narrow pulse pressure was associated with slowed information processing in PASC patients compared to healthy controls (−1.5, p = 0.04). Furthermore, increased heart rate during the orthostatic challenge was associated with a decreased procedural reaction time in PASC and < 4 year ME/CFS patients who were 40 to 65 years of age. Discussion For PASC patients, both their disease state and hemodynamic changes during orthostatic challenge were associated with slower reaction time and decreased response accuracy during cognitive testing. Reduced cognitive efficiency in <4 year ME/CFS patients was associated with higher heart rate in response to orthostatic stress. Hemodynamic changes did not correlate with cognitive impairment for >10 year ME/CFS patients, but cognitive impairment remained. These findings underscore the need for early diagnosis to mitigate direct hemodynamic and other physiological effects on symptoms of cognitive impairment.